INDIAN-BRITISH: DILEMMA OF KARIMâ€™S WORLD IN THE NOVEL THE BUDDHA OF SUBURBIA BY HANIF KUREISHI - Supit, Alfa Selkli Indira (LINGUAMEDIA Journal, 2021)
This research purposes to explain the dilemma experienced by Karim, the main character in the novel The Buddha of Suburbia. The objectives of this research are to find out the kind of dilemma faced by Karim as an Indian-British marriage child and how he faces it. This research is a descriptive qualitative study and uses a mimetic theory by M.H. Abrams with an extrinsic element approach. The data of this research are all things taken from the novel in the form of text and dialogues of the main character. Based on the data analysis, the writer found the results as follows: There are four things that constitute the dilemmas of Karim, i.e. national identity, sexuality, family, and the place where Karim lives. The conclusion shows that family takes the biggest role to create and heal the dilemmas due to living in a multicultural society. Through the literary work readers can see that what is written in the novel is a reflection of the real condition of the society.Â Keywords: Dilemmas, Main Character, Mix-Marriage, Multicultural Society, and Literary Work.